Analisis Faktor Yang Berhubungan Dengan Pelaksanaan Phbs Tatanan Rumah Uptd Puskesmas Batumarta II Oku Tahun 2021 - Afua Amuri; Erma Gustina; Atma Deviliawati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
PHBS in household arrangements is one of the strategies launched by the Ministry of Health to achieve the Millennium 2016 sustainable development goals through the formulation of a healthy Indonesia vision and mission in welcoming Sustainable Development Goals Based on the RKT of the South Sumatra Health Office, the 2019 Percentage of Households with PHBS in 2018 was targeted at 60% and realized 64% or 106.67%. OKU Regency in 2020 was (71.56%) with the lowest PHBS achievement in Lubuk Raja District, Batumarta II Health Center Working Area of ??55.36% and followed by East Baturaja Subdistrict, Sekar Jaya of 58,51% .Health Center Working Area.factors related to the implementation of a clean and healthy lifestyle (PHBS) in household arrangements in the work area of ??the Komering Ulu District Health Office in 2021. This research method uses a quantitative method with a cross sectional design. Sampling using purposive sampling totaling 100 respondents. The results showed that there was a relationship between Knowledge, p-value 0.028, Attitude p-value 0.006. Permanent Employment p-value 0.006. and Health Officer support p-value 0.040.. with the implementation of household PHBS. The most dominant factor is occupation with a p-value of 0.001. the most dominant factor of work p-value 0.001, It is suggested that the puskesmas or related parties are expected to provide counseling funds and conduct training for health cadres and housewives on a scheduled basis so that they can increase the scope of PHBS in household arrangements in the working area of ??UPTD Puskesmas Batumarta II